High temperature and low voltage AC poling for 0.24Pb(In1/2Nb1/2)O3-0.46Pb(Mg1/3Nb2/3)O3-0.30PbTiO3 piezoelectric single crystals manufactured by continuous-feeding Bridgman method - Cong Luo; Tomoaki Karaki; Yohachi (John) Yamashita; Jiayue Xu (Journal of Materiomics, 2021)
Alternating current poling (ACP) in air by changing poling temperature (70–130 °C) and voltages (2–6 kVrms/cm) on pseudo-ternary 0.24 Pb(In1/2Nb1/2)O3-0.46 Pb(Mg1/3Nb2/3)O3-0.30PbTiO3 (PIMN-0.30PT) single crystals (SCs) manufactured by continuous-feeding Bridgman (CF BM) method was investigated. Free dielectric permittivity (εT33/ε0) and piezoelectric constant (d33) were improved to be 7000 and 2340 pC/N, which were 29% higher than those of direct current poling (DCP) at 90 °C with 4 kV/cm (εT33/ε0 = 5440, d33 = 1810 pC/N). However, phase change temperature (Tpc) decreased from 94 °C to 78 °C as opposite results reported by other groups. We demonstrated that the high temperature (HT) ACP improved piezoelectric performance of CF BM SCs, however, the Tpc were different from other crystal growth method. The well-designed ACP process was a promising method for mass production not only to enhance the electrical properties for the pseudo-ternary SCs but also reduce the risk of breakdown and realizes organic solvent-free poling process.